Is the doctrine of double effect irrelevant in end-of-life decision making? - Allmark, Peter (Nursing philosophy, 2010)
In this paper, we consider three arguments for the irrelevance of the doctrine of double effect in end-of-life decision making. The third argument is our own and, to that extent, we seek to defend it. The first argument is that end-of-life decisions do not in fact shorten lives and that therefore there is no need for the doctrine in justification of these decisions. We reject this argument; some end-of-life decisions clearly shorten lives. The second is that the doctrine of double effect is not recognized in UK law (and similar jurisdictions); therefore, clinicians cannot use it as the basis for justification of their decisions. Against this we suggest that while the doctrine might have dubious legal grounds, it could be of relevance in some ways, e.g. in marking the boundary between acceptable and unacceptable practice in relation to the clinician's duty to relieve pain and suffering. The third is that the doctrine is irrelevant because it requires there to be a bad effect that needs justification. This is not the case in end-of-life care for patients diagnosed as dying. Here, bringing about a satisfactory dying process for a patient is a good effect, not a bad one. What matters is that patients die without pain and suffering. This marks a crucial departure from the double-effect doctrine; if the patient's death is not a bad effect then the doctrine is clearly irrelevant. A diagnosis of dying allows clinicians to focus on good dying and not to worry about whether their intervention affects the time of death. For a patient diagnosed as dying, time of death is rarely important. In our conclusion we suggest that acceptance of our argument might be problematic for opponents of physician-assisted death. We suggest one way in which these opponents might argue for a distinction between such practice and palliative care; this relies on the double-effect doctrine's distinction between foresight and intention.